Antifungal Activity of Auricularia nigricans Methanol Extract against Candida parapsilosis using The Well Method : Aktivitas Antifungi Ekstrak Metanol Auricularia nigricans Terhadap Candida parapsilosis dengan Metode Sumuran - Septiani Resika Dewi; Floreta Fiska Yuliarni (Akademi Farmasi Surabaya, 2023)
This study aims to determine the ability of the methanol extract of the fungus Auricularia nigricans to inhibit the growth of Candida parapsilosis. The extraction method used was maceration with the antifungal test method, namely the well method, the concentrations used were 0.2g/mL, 0.3g/mL, 0.4g/mL and 10% DMSO as a negative control. The results of the study showed that all concentrations used did not form inhibition zones. This result is included in the inactive category. So that Auricularia nigricans does not have antifungal activity against Candida parapsilosis.